Risk management and financial institutions - Hull, John , 1946- (Hoboken, New Jersey : Wiley, 2015)
The most complete, up to date guide to risk management in finance Risk Management and Financial Institutions explains all aspects of financial risk and financial institution regulation, helping readers better understand the financial markets and potential dangers. This new fourth edition has been updated to reflect the major developments in the industry, including the finalization of Basel III, the fundamental review of the trading book, SEFs, CCPs, and the new rules affecting derivatives markets. There are new chapters on enterprise risk management and scenario analysis.